Vernakalant in Atrial Fibrillation: A Relatively New Weapon in the Armamentarium Against an Old Enemy - Antoine Kossaify (AboutScience Srl, 2019)
Atrial fibrillation is the most common sustained cardiac arrhythmia, and its prevalence is increasing with age; also it is associated with significant morbidity and mortality. Rhythm control is advised in recent-onset atrial fibrillation, and in highly symptomatic patients, also in young and active individuals. Moreover, rhythm control is associated with lower incidence of progression to permanent atrial fibrillation. Vernakalant is a relatively new anti-arrhythmic drug that showed efficacy and safety in recent-onset atrial fibrillation. Vernakalant is indicated in atrial fibrillation (⩽7 days) in patients with no heart disease (class I, level A) or in patients with mild or moderate structural heart disease (class IIb, level B). Moreover, Vernakalant may be considered for recent-onset atrial fibrillation (⩽3 days) post cardiac surgery (class IIb, level B). Although it is mainly indicated in patients with recent-onset atrial fibrillation and with no structural heart disease, it can be given in moderate stable cardiac disease as alternative to Amiodarone. Similarly to electrical cardioversion, pharmacological cardioversion requires a minimal evaluation and cardioversion should be included in a comprehensive management strategy for better outcome.